Activation policies in Germany: from status protection to basic income support - Werner Eichhorst; Maria Grienberger-Zingerle; Regina Konle-Seidl (Institute for the Study of Labor (IZA), 2006)
This paper provides an overview of the sequential shift towards activating labor market and social policy in Germany. It not only shows the changes in the instruments of active and passives labor market policies but also analyzes the implications of this change for the political economy, the governance and the legal structure of a Bismarckian welfare state. Our study points at the changes in Germany's status- and occupation-oriented unemployment benefit regime that has been relinquished for a larger share of dependent population. Unemployment insurance benefit duration is shorter now and newly created basic income support for needy persons is not earnings-related anymore. Pressure on unemployed to take up jobs has increased considerably while more persons than before have access to employment assistance. The paper also aims at a preliminary assessment of the effects of activating labor market policy on labor market as well as social outcomes and sets out probable paths of future adaptation.
urn:nbn:de:101:1-2008050508
Keywords: 330; Arbeitslosenversicherung; Hartz-Reform; Soziale Mindestsicherung; Arbeitsmarktpolitik; Wirkungsanalyse; Deutschland